Circadian phase-dependent antinociceptive reaction in mice determined by the hot-plate test and the tail-flick test after intravenous injection of dalargin-loaded nanoparticles - Ramge, Peter; Kreuter, Jörg; Lemmer, Björn (Chronobiology international, 1999)
Peptides normally do not cross the blood-brain barrier (BBB). Previously, it has been shown that the hexapeptide enkephalin analogue dalargin with polysorbate-80-coated nanoparticles (DAL/NP) can be transported across the BBB and is able to exhibit an antinociceptive effect in mice. In the present study, the circadian time and dose dependencies of the antinociceptive effect of different dalargin preparations were investigated. The active preparation (DAL/NP, 5 mg/kg, 10 mg/kg), as well as a dalargin solution in phosphate buffered saline (DAL/SOL, 10 mg/kg) were injected intravenously to groups of 10-12 inbred DBA/2 mice at 12 different circadian times; mice were synchronized to a light-dark (LD) 12:12 regimen. The antinociceptive effect was determined 15 minutes postinjection by the hot-plate test. Experiments with DAL/NP were repeated using the tail-flick test system at two selected times (08:00 and 20:00) to test for dose dependency (2.5, 5, 7.5, 10 mg/kg). Hot-plate latencies were rhythmic under baseline and after DAL/SOL, with acrophases in the dark phase; DAL/SOL did not influence latency time. In contrast, DAL/NP significantly increased reaction time dose dependency; the maximal possible effect was rhythmic with the 10 mg/kg preparation, with a peak effect in the early light phase. Results were confirmed by the tail-flick test. The experiments demonstrate that an enkephalin analogue coated with nanoparticles can easily cross the BBB and is able to display a dose- and time-dependent antinociceptive effect.